The Three Death Sentences of Clarence Henderson: A Battle for Racial Justice at the Dawn of the Civil Rights Era - Joyner, Chris (Abrams, Inc., 2022)
Cover -- Title Page -- Copyright Page -- Dedication -- Contents -- Preface -- Chapter 1: Murder and Chaos -- Chapter 2: Carrollton -- Chapter 3: A Desperate Manhunt -- Chapter 4: "A Very Dark Negro" -- Chapter 5: The First Trial -- Chapter 6: "Let Me Go Home" -- Chapter 7: Subversive Elements -- Chapter 8: The Commies Come to Town -- Chapter 9: "His Fight Is Our Fight" -- Chapter 10: The NAACP Takes Charge -- Chapter 11: A New Trial Ordered -- Chapter 12: Dan Duke -- Chapter 13: The Second Trial -- Chapter 14: Ballistics, Nan, and a Verdict -- Chapter 15: New Evidence, New Trial -- Chapter 16: The Third Trial -- Chapter 17: Cornett v. Jones -- Chapter 18: God and the NAACP -- Acknowledgments -- Notes -- Index of Searchable Terms.